Gender and Transparency Analysis in Public Service: Integrating Public Satisfaction and Corruption Perception at Balai Litbang Agama of Semarang - Jabbar, Abdul; Ariningrum, Novita Dwi; Nor Amelia, Rizki; Sriyanto, Nanto (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2026)
This study investigates the relationship between the Corruption Perception Index (CPI) and the Community Satisfaction Index (CSI) at Balai Litbang Agama (the Office of Religious Research and Development) of Semarang, with particular attention to gender differences. A total of 155 respondents participated in the survey. The statistical analysis reveals no significant gender differences in either corruption perception or public satisfaction. It also indicates a moderate positive correlation between transparency measures and public satisfaction, suggesting that improved governance practices enhance public trust. These findings demonstrate the effectiveness of standardized service delivery protocols and highlight the importance of transparency initiatives in public service institutions. In addition, they underscore the role of effective governance and the importance of gender-responsive reforms in ensuring equitable service access and reducing corruption risks. This study contributes to the literature on gender-inclusive governance and provides practical insights for the development of equitable public service policies. The study concludes that systematic transparency measures can serve as effective tools for improving both service quality and public trust across diverse demographic groups.